Efeito fotobiomodulador da terapia com diodo emissor de luz de baixa intensidade na inflamação muscular induzida por exercício em ratos - Vasconcelos, Alan Bruno Silva (2017)
INTRODUCTION - The biological effects of low intensity light sources, such as light emitting diode therapy (LEDT), indicate that phototherapy is a method for obtaining ergogenic and recuperative effects of skeletal muscle. However, clinical trials and experimental researches differ in respect to the parameters to be used. OBJECTIVE - To compare different doses of the LED (630 nm) in the inflammation of striated skeletal muscle induced by exercise in rats. METHODS - Wistar rats were divided in five experimental groups (n=8/group): control (CON), the animals were not submitted to exercise protocol; passive recovery (RP), the animals received no treatment after induction of inflammation; LEDT (1.2 J, 4.2 J or 10.0 J), the animals were submitted to phototherapy after induction of inflammation. Skeletal muscle inflammation was induced by a protocol of 100 minutes of swimming. After exercise, the animals in the LEDT groups were exposed to phototherapy at the doses of 1.2 J, 4.2 J or 10.0 J on the triceps sural muscles (gastrocnemius and soleus). For evaluation of mechanical hyperalgesia by electronic von Frey, the animals were submitted to evaluation before and at 24 hours after swimming procedure. After 24 hours of swimming, blood samples were collected to measure creatine kinase (CK) activity. The soleus muscle was removed for histological analysis. Data were expressed as mean ± standard error of mean (S.E.M). Analysis of variance was used followed by Tukey post hoc. The histological data were performed with chi-square analysis followed by correction of Yates. This study was approved by the Ethics Committee on Research with Animals (Federal University of Sergipe) under n°. 15/2013 and by the Ethics Committe in the Use of Animals (State University of Londrina) under nº 124/2014. RESULTS - The plasma activity of CK was increased (p <0.0001) in the PR group (2071 ± 346 U / L) when compared to the CON group (683 ± 103 U / L) and attenuation (p <0.0001) of this response was observed in the LEDT (630 nm)-treated groups at the doses of 1.2 J (379 ± 71 U / L), 4.2 J (599 ± 131 U / L) or 10.0 J (544 ± 86 U / L). Regarding mechanical hyperalgesia, the PR group presented a reduction (p <0.005) in the paw withdrawal threshold (-11.9 ± 1.9 g) when compared to the CON group (2.2 ± 1.5 g). Only LEDT 4.2 J (-3.3 ± 2.4 g) altered this threshold (p <0.05) when compared to the PR group. In the histological analysis, leukocyte infiltration was observed in the muscle of animals from the PR group, in addition to areas of edema and necrosis. However, lower infiltration was observed in the animals treated with doses of 4.2 and 10.0 J. CONCLUSION: The application of LEDT (630 nm) reduces the inflammatory lesion in muscle fibers of rats submitted to exercise. The dose of 4.2 J induced better anti-inflammatory and antinociceptive effects than doses of 1.2 and 10.0 J.